2019
DOI: 10.1016/j.lindif.2019.101783
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect contributions of executive function to word decoding and reading comprehension in kindergarten

Abstract: Extant research is increasingly recognizing the contribution of executive function (EF) to reading comprehension alongside established predictors like word decoding and oral language. The nature of the association between EF and reading comprehension is commonly investigated in older children and in those with reading impairments. However, less is known about this relationship in emerging readers in kindergarten, where word decoding and reading comprehension are highly intertwined. Moreover, a better understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 85 publications
6
15
0
Order By: Relevance
“…In this study the contribution of the fluent decoding skills to reading comprehension was much stronger than the effects of oral language skills. These findings suggest that the effects of the executive functions on reading comprehension could be stronger via decoding skills (Haft et al, 2019;Spencer et al, 2019) but they also support our findings by suggesting that these effects decrease as the students become better decoders.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study the contribution of the fluent decoding skills to reading comprehension was much stronger than the effects of oral language skills. These findings suggest that the effects of the executive functions on reading comprehension could be stronger via decoding skills (Haft et al, 2019;Spencer et al, 2019) but they also support our findings by suggesting that these effects decrease as the students become better decoders.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with other studies from transparent orthographies (Tobia & Bonifacci, 2015;Torppa et al, 2016), and in contrast to other studies from opaque orthographies that sampled students from this age group (e.g., Kim, 2017) we expected oral language skills to have stronger effects and fluent decoding skills to have weaker effects on the development of reading comprehension. Furthermore, since we expected our students to have strong fluent decoding skills by 2nd grade and executive functions were found to affect students' performance in reading comprehension indirectly mostly via decoding skills (Haft et al, 2019;Spencer et al, 2019), we expected that the executive functions would not have a strong direct effect on reading comprehension.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, it is the ability to segment words. Ehri (2005) as cited in (Haft et al, 2019) states that word decoding refers to simple mapping printed words to sound, but in reality, it involves numbers of lexical and sublexical processes including phonological and orthographic processes. On the other hand, Encoding is a process of using the decoded information to create new words.…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades, studies revealed that executive function (EF) has consistently associated with reading comprehension and significantly accounted for the individual differences in reading performance beyond the contribution of decoding skills (e.g., Butterfuss & Kendeou, 2018; Cantin, Gnaedinger, Gallaway, Hesson‐Mclnnis, & Hund, 2016; Kieffer, Vukovic, & Berry, 2013; Nouwens, Groen, & Verhoeven, 2016). Despite evidence suggesting the significance of EF to reading (e.g., Arrington, Kulesz, Francis, Fletcher, & Barnes, 2014; Hung & Loh, in press; Kieffer et al, 2013), many questions still await to be answered (see the review of Butterfuss & Kendeou, 2018), in particular the lack of clarity on the mechanism by which EF contributes to reading comprehension (Cirino et al, 2019; Haft et al, 2019; Kim, 2017; Nouwens, Groen, Kleemans, & Verhoeven, in press). Recently, Kim (2020) proposed a hypothetical model (Direct and Indirect Effects Model of Reading (DIER)) to illustrate how EF contributes to reading comprehension.…”
Section: Introductionmentioning
confidence: 99%